2020
DOI: 10.25095/mufad.740040
|View full text |Cite
|
Sign up to set email alerts
|

Katılım Bankalarının Finansal Performanslarının ELECTRE Yöntemiyle Analizi

Abstract: Genel ekonomi içerisinde önemli işlevler gören bankaların, mali yapılarının doğru ve güvenilir bir biçimde analiz edilip, değerlendirilerek ilgili bilgi kullanıcılarına sunulması gerekmektedir. Çalışmanın amacı, Türkiye'de bankacılık sektöründe yeni sayılabilecek katılım bankalarının finansal performanslarının çok kriterli karar verme tekniklerinden ELECTRE (ELimination and Choice Translating REality) yöntemiyle ölçülerek değerlendirilmesidir. Çalışmaya Türkiye'de faaliyet gösteren, beş katılım bankasının tama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…According to the GRA results based on entropy, between 2019-2021, Ziraat Participation and Vakıf Katılım showed the most successful performance, while Albaraka Türk showed the lowest performance. These results are compared with the literature, with the studies of Bektaş (2021) and Çelik (2020) for Ziraat Participation, and Gençtürk et al (2021), Odabaş and Bozdoğan (2020), Karavardar andÇilek (2020), andAyrçay et al (2017) is in line with the studies. Albaraka Türk's lowest performance was found in Yurttadur et al (2022), Bektaş (2021), Odabaş and Bozdoğan (2020), Karakaya (2020) and Gezen (2019) are in line with the studies.…”
Section: Tesamsupporting
confidence: 80%
See 1 more Smart Citation
“…According to the GRA results based on entropy, between 2019-2021, Ziraat Participation and Vakıf Katılım showed the most successful performance, while Albaraka Türk showed the lowest performance. These results are compared with the literature, with the studies of Bektaş (2021) and Çelik (2020) for Ziraat Participation, and Gençtürk et al (2021), Odabaş and Bozdoğan (2020), Karavardar andÇilek (2020), andAyrçay et al (2017) is in line with the studies. Albaraka Türk's lowest performance was found in Yurttadur et al (2022), Bektaş (2021), Odabaş and Bozdoğan (2020), Karakaya (2020) and Gezen (2019) are in line with the studies.…”
Section: Tesamsupporting
confidence: 80%
“…These results are compared with the literature, with the studies of Bektaş (2021) and Çelik (2020) for Ziraat Participation, and Gençtürk et al (2021), Odabaş and Bozdoğan (2020), Karavardar andÇilek (2020), andAyrçay et al (2017) is in line with the studies. Albaraka Türk's lowest performance was found in Yurttadur et al (2022), Bektaş (2021), Odabaş and Bozdoğan (2020), Karakaya (2020) and Gezen (2019) are in line with the studies. In addition to these, according to the results of the analysis, it can be concluded that state participation banks performed better than private participation banks between the years 2019-2021.…”
Section: Tesamsupporting
confidence: 80%
“…Ultimately, the present study found that Vakıf Participation Bank had the highest performance in 2018. Çilek and Karavardar (2020); In the studies conducted by Odabaş and Bozdoğan (2020), the bank with the best performance in 2018 was determined to be Vakıf Bank, Ziraat Participation Bank in 2019-2020. Eid (2021); Yurttadur and Taşçı (2022); In the studies conducted by Şekkeli and Güçlü (2023), Ziraat Katılım Bank is the bank with the best performance for the same periods.…”
Section: Discussionmentioning
confidence: 99%